2020
DOI: 10.1177/0038040720928484
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Dreams: Occupational Plans and Gender Differences in STEM Major Persistence and Completion

Abstract: In the United States, women are more likely than men to enter and complete college, but they remain underrepresented among baccalaureates in science-related majors. We show that in a cohort of college entrants who graduated from high school in 2004, men were more than twice as likely as women to complete baccalaureate degrees in science, technology, engineering, and mathematics (STEM) fields, including premed fields, and more likely to persist in STEM/biomed after entering these majors by sophomore year. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 44 publications
1
34
0
4
Order By: Relevance
“…Negatively speaking, science popularization hinders higher education development or competitiveness to some degree. Firstly, science popularization increases gender inequality in higher education systems; it is found that science popularization has different impacts on different genders, and female students are less interested in science popularization activities than male students so that gender imbalance caused by science popularization may occur and higher education competitiveness, which requires gender equality, is likely to decline [ 10 , 34 , 35 ]. Secondly, lacking sufficient focus on science popularization is likely to decrease higher education competitiveness; science popularization activities are good opportunities for students to learn new skills or knowledge, and lacking enough related activities reduces studying chances and competitiveness of college students, which in turn reduces higher education competitiveness [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Negatively speaking, science popularization hinders higher education development or competitiveness to some degree. Firstly, science popularization increases gender inequality in higher education systems; it is found that science popularization has different impacts on different genders, and female students are less interested in science popularization activities than male students so that gender imbalance caused by science popularization may occur and higher education competitiveness, which requires gender equality, is likely to decline [ 10 , 34 , 35 ]. Secondly, lacking sufficient focus on science popularization is likely to decrease higher education competitiveness; science popularization activities are good opportunities for students to learn new skills or knowledge, and lacking enough related activities reduces studying chances and competitiveness of college students, which in turn reduces higher education competitiveness [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For first-generation college students, female students are less likely to choose male-dominated majors (Wright, 2019) and to persist in STEM major completion (Mau, 2016). Weeden et al (2020) used a national longitudinal data set and found substantial gender differences in STEM major completion. Specifically, among 2004 high school graduates who enrolled in college in the following fall, 18% of male graduates majored in the STEM/biomed field compared to 7.9% of female graduates.…”
Section: Poverty Level: Free-lunch High-school Student Participationmentioning
confidence: 99%
“…Researchers have proposed multiple factors that may affect the attrition of women in STEM, such as a lack of women role models [ 51 ]. However, a more insidious and deep-rooted problem seems to be gender-based stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Among primary school children, the differences in perceived competencies in STEM are negligible [ 52 ]. Yet, as girls mature, the perceived gender differences in science acuity increase such that most girls have self-selected out of STEM careers by the time they leave high school [ 48 , 51 ]. Reshma Saujani, who founded a charitable organization called “Girls Who Code,” believes that “women have been socialized to aspire to perfection and as a result are overly cautious,” resulting in a fear of failure, which dampens their questioning nature and prevents a sense of fulfillment in STEM careers [ 53 ].…”
Section: Introductionmentioning
confidence: 99%